Bio-Based Nitriles from the Heterogeneously Catalyzed Oxidative Decarboxylation of Amino Acids - Claes, Laurens; Matthessen, Roman; Rombouts, Ine; Stassen, Ivo; De Baerdemaeker, Trees; Depla, Diederik; Delcour, Jan A.; Lagrain, Bert; De Vos, Dirk E. (ChemSusChem, 2015)
The oxidative decarboxylation of amino acids to nitriles was achieved in aqueous solution by in situ halide oxidation using catalytic amounts of tungstate exchanged on a [Ni,Al] layered double hydroxide (LDH), NH4Br, and H2O2 as the terminal oxidant. Both halide oxidation and oxidative decarboxylation were facilitated by proximity effects between the reactants and the LDH catalyst. A wide range of amino acids was converted with high yields, often >90 %. The nitrile selectivity was excellent, and the system is compatible with amide, alcohol, and in particular carboxylic acid, amine, and guanidine functional groups after appropriate neutralization. This heterogeneous catalytic system was applied successfully to convert a protein‐rich byproduct from the starch industry into useful bio‐based N‐containing chemicals. Going the extra nitrile: A catalytic system that consists of a tungstate‐exchanged layered double hydroxide and a bromide salt is developed for the oxidative decarboxylation of amino acids under mild conditions using H2O2 as a green oxidant. Several functional groups are tolerated, and the nitrile selectivity is often 99 %. This strategy offers opportunities for protein‐rich biomass valorization.